2015
DOI: 10.1016/j.proci.2014.06.047
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and modelling study of speciation and benzene formation pathways in premixed 1-hexene flames

Abstract: An existing detailed and broadly validated kinetic scheme is augmented to capture the flame chemistry of 1-hexene under stoichiometric and fuel rich conditions including benzene formation pathways. In addition, the speciation in a premixed stoichiometric 1-hexene flame (flat-flame McKenna-type burner) has been studied under a reduced pressure of 20-30 mbar applying flame-sampling molecular-beam time-offlight mass spectrometry and photoionization by tunable vacuum-ultraviolet synchrotron radiation. Mole fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 42 publications
0
14
0
1
Order By: Relevance
“…The pathways for benzene formation via fulvene were discussed in detail in a recent study on 1-hexene flame chemistry [52]. In that work the fulvene chemistry has been included and the thermodynamic data of several species including C 3 H 3 (propargyl), C 3 H 4 (allene), C 3 H 4 P (propyne), C 3 H 5 (allyl), C 3 H 6 , n-C 3 H 7 , and i-C 3 H 7 have been updated.…”
Section: Chemical Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The pathways for benzene formation via fulvene were discussed in detail in a recent study on 1-hexene flame chemistry [52]. In that work the fulvene chemistry has been included and the thermodynamic data of several species including C 3 H 3 (propargyl), C 3 H 4 (allene), C 3 H 4 P (propyne), C 3 H 5 (allyl), C 3 H 6 , n-C 3 H 7 , and i-C 3 H 7 have been updated.…”
Section: Chemical Modelmentioning
confidence: 99%
“…This means that many intermediate C 2 , C 3 , C 4 , and C 5 species are formed by various pathways. This complexity is an effect of the fuel molecule's size and very different to the much simpler flame chemistry of butane, butene isomers and even 1-hexene, which were studied with older versions of the kinetic model [29,30,52]. Among the various decomposition pathways, two main threads of C-atom mass flows may be distinguished.…”
Section: N-heptane Consumptionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is evident that the predictive capabilities of the PAH sub-model rely on the accuracy of the description of the formation of the first aromatic ring. Already this first step in the overall soot formation process can be very complex: Normally, benzene is considered to be this first aromatic ring and its formation is generally described by reactions of resonantly stabilized radicals like propargyl (C 3 H 3 ), allyl (C 3 H 5 ), i-C 4 H 5 , and cyclopentadienyl (C 5 H 5 ) [5,[13][14][15][16][17][18][19]. However, precursors and reactions have been identified that can form aromatic species without passing through benzene, and it is therefore important to note that benzene is not necessarily the first aromatic ring [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the fulvene chemistry was added as described in Ref. [27]. In total, 70 species and 273 reactions were newly incorporated.…”
Section: Combustion Chemistry Modelingmentioning
confidence: 99%